Do the Modules Meet the Need? A Study of Students’ Reading Text Skills in the Digital English Era - Yulianto Sabat; Abd Syakur; Rizki Prasetya; Moh Hilman Fikri (CV FOUNDAE, 2024)
This study addresses the crucial issue of low reading proficiency among English language students. It investigates the impact of digital modules on enhancing reading skills using a quasi-experimental quantitative design with a sample of 80 students randomly selected from a population of 450. The results, analyzed through ANOVA, reveal a significant improvement in reading skills, with digital modules providing an effective and engaging learning tool. This research highlights the potential of technology-driven interventions in addressing literacy challenges and offers valuable insights for integrating digital modules into higher education to improve academic outcomes.